2020
DOI: 10.1115/1.4045915
|View full text |Cite
|
Sign up to set email alerts
|

REEF3D::FNPF—A Flexible Fully Nonlinear Potential Flow Solver

Abstract: In situations where the calculation of ocean wave propagation and impact on structures are required, fast numerical solvers are desired in order to find relevant wave events. Computational fluid dynamics (CFD)-based numerical wave tanks (NWTs) emphasize on the hydrodynamic details such as fluid–structure interaction, which make them less ideal for the event identification due to the large computational resources involved. Therefore, a computationally efficient numerical wave model is needed to identify the eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Also, the complication of solving for two-phase fluid flows in OpenFOAM may be a source of error that should not be factored out. To confirm these findings and be able to identify credibly the sources of the errors, other suitable solvers can be used that employ similar equations and modelling approaches as these of the present work [66,67].…”
Section: Discussionmentioning
confidence: 59%
“…Also, the complication of solving for two-phase fluid flows in OpenFOAM may be a source of error that should not be factored out. To confirm these findings and be able to identify credibly the sources of the errors, other suitable solvers can be used that employ similar equations and modelling approaches as these of the present work [66,67].…”
Section: Discussionmentioning
confidence: 59%
“…From wave gauges 1 to 4, the x-coordinates are x = 19.8, 20.8, 21.8 and 22.1 m. The simulations are computed with four 2.7 GHz Intel Xeon E5 cores on Mac Pro for REEF3D::FNPF and REEF3D::SFLOW and 128 2.1 GHz Intel E5-2683v4 cores on the supercomputer Fram. The grid convergence study for the three models REEF3D::CFD, REEF3D::SFLOW and REEF3D::FNPF were reported respectively by Bihs et al [1], Wang et al [47] and Bihs et al [51]. As a result, the dx = 0.005 m, dx = 0.005 m and dx = 0.005 m are used in the REEF3D::CFD, REEF3D::SFLOW and REEF3D::FNPF simulations respectively.…”
Section: Two-dimensional Wave Breaking Over a Mild Slopementioning
confidence: 99%
“…The new numerical wave model FNPF of REEF3D solves the Laplace equation for the flow potential and the nonlinear kinematic and dynamics free surface boundary conditions [15]. Very promising results in the reproduction of experimental regular and bi-chromatics wave with constant water depth as well as with complex bottom topology have been presented with the open-source hydrodynamic model REEF3D::FNPF in [16] and [17]. This approach requires reduced computational resources compared to CFD based NWTs.…”
Section: Introductionmentioning
confidence: 99%